2014
DOI: 10.1186/1471-2180-14-56
|View full text |Cite
|
Sign up to set email alerts
|

Species-specific viability analysis of Pseudomonas aeruginosa, Burkholderia cepacia and Staphylococcus aureus in mixed culture by flow cytometry

Abstract: BackgroundBacterial species coexist commonly in mixed communities, for instance those occurring in microbial infections of humans. Interspecies effects contribute to alterations in composition of communities with respect to species and thus, to the course and severity of infection. Therefore, knowledge concerning growth and viability of single species in medically-relevant mixed communities is of high interest to resolve complexity of interspecies dynamics and to support development of treatment strategies. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 54 publications
(75 reference statements)
2
16
0
Order By: Relevance
“…Flow cytometry can also be applied to quantify viability of different bacterial species after resuspension of multispecies biofilms. As an example, the viability of P. aeruginosa , B. cepacia , and S. aureus in a mixed culture was quantified by means of fluorescence detection using multifluorescent labeling with antibody, lectins, SYBR Green and propidium iodide ( Rüger et al, 2014 ). This method has also been applied to P. aeruginosa axenic biofilms in order to separate active and dormant cell populations and compare their phenotypes and resistance to various antimicrobial agents ( Kim et al, 2009 ).…”
Section: Experimental Methods To Study Multispecies Biofilms and Theimentioning
confidence: 99%
“…Flow cytometry can also be applied to quantify viability of different bacterial species after resuspension of multispecies biofilms. As an example, the viability of P. aeruginosa , B. cepacia , and S. aureus in a mixed culture was quantified by means of fluorescence detection using multifluorescent labeling with antibody, lectins, SYBR Green and propidium iodide ( Rüger et al, 2014 ). This method has also been applied to P. aeruginosa axenic biofilms in order to separate active and dormant cell populations and compare their phenotypes and resistance to various antimicrobial agents ( Kim et al, 2009 ).…”
Section: Experimental Methods To Study Multispecies Biofilms and Theimentioning
confidence: 99%
“…Therefore, several offline methods have been applied offering a lower information density in comparison to an online signal. This includes the utilization of molecular methods such as quantitative terminal restriction fragment length polymorphism (Rüger, Ackermann, & Reichl, 2014) and quantitative real time polymerase chain reaction (Pérez et al, 2015) for the biomass measurement.…”
mentioning
confidence: 99%
“…This striking negative clinical correlation between S. aureus and P. aeruginosa during teenage years and young adulthood has driven several in vitro and in vivo studies geared toward characterizing the interbacterial interactions of these two organisms (36)(37)(38)(39)(40)(41)(42)(43)(44). These previous studies have found that P. aeruginosa secretes various antistaphylococcal products and proteases, such as LasA, that can cause both biofilm dispersion and cell lysis of S. aureus (42,45).…”
mentioning
confidence: 99%